Analisis Kinerja Bidan dalam Pelayanan Antenatal Care di Rumah Sakit Ibu dan Anak Marissa Plaju - Tri Eka Kandesta; Erma Gustin; Helen Evelina Siringoringo (Jurnal Kesehatan Saelmakers PERDANA, 2023)
Fund (UNICEF) revealed that more than 290,000 women died from complications of pregnancy and childbirth in 2019 and that 2.8 million pregnant women and newborns die every year, or death every 11 seconds. Midwifery services are carried out by hospital midwives, one of which is the antenatal care examination which is carried out to check the condition of the mother and fetus on a regular basis. The impact if the midwife is not optimal can cause harm to the mother and fetus. This study aims to determine the analysis of the performance of hospital midwives in ANC services at the Marissa Plaju Mother and Child Hospital (RSIA) Palembang in 2022. It was carried out in May – June 2022. This study was quantitative with a cross sectional design, the population of this study were all midwives of RSIA Marissa. Plaju amounted to 49 samples. Data collection and retrieval using a questionnaire. The results of statistical test analysis using chi-square statistical tests and multiple logistic regression where the results show there is a significant relationship (p value <0.05) for the variables of knowledge (0.000), attitudes (0.001), training (0.002), infrastructure (0.000), and motivation (0.000). There is no relationship between the variable length of service (0.111). From the results of multivariate statistical tests, it was found that the dominant factor in the performance of hospital midwives in ANC services was attitude (p = 0.995; OR = 4.137). It is recommended to hospital midwives by giving a positive attitude to patients by providing counseling in the form of socialization